Adjustment with a human face: Evidence from Jamaica - Handa, Sudhanshu; King, Damien (International Food Policy Research Institute, 1998)
In September 1991 Jamaica liberalized its exchange rate as part of its Structural Adjustment Program (SAP). The sudden and steep devaluation associated with this policy move had serious repercussions for real purchasing power, poverty, general inflation, and food prices, especially staple foods such as rice and flour which are imported. This study evaluates the ‘social cost’ of the liberalization policy by examining the behavior of pre-school children’s weight for height or wasting, an indicator of nutritional status that is sensitive to short term fluctuations in living conditions. Using 7 years of national micro survey data, we apply ‘synthetic cohort’ analysis to disentangle the separate impacts of child’s age, date of birth, and survey year on weight for height.